PRODUCTIVE ZAKAT DISTRIBUTION WITH SOCIAL ENTREPRENEURSHIP THROUGH COMMUNITY-BASED AMIL ZAKAT INSTITUTIONS - Novi Amaliah; M Makhrus (FEBI Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
In order to distribute productive zakat with social entrepreneurship through institutions based on community organizations called amil zakat in the Banyumas Regency, this research aims to understand the distribution process as well as the encouraging and discouraging elements. Field research using a descriptive qualitative research methodology is the method used. using methods for gathering data include observation, documenting, and interviewing. In order to make the data from interviews, field notes, documentation, and other sources easier to understand and to produce conclusions that can be shared with the larger community, data analysis is done by methodically searching and assembling the data. The study's findings demonstrate how the effective zakat distribution program has aided in the empowerment and development of the local economy. Amil zakat institutions, specifically LAZISMU and LAZISNU, carry out the form of productive zakat distribution with social entrepreneurship in the form of business capital aid that enables mustahik to expand their enterprises. The availability of cash or productive zakat programs with the excitement of the community (mustahik) are supporting variables in the distribution of productive zakat with social entrepreneurship by amil zakat institutions. While the community spends a large portion of its productive zakat earnings on consumptive necessities, the limiting element is the lack of mentorship intensity.